THE IMPLEMENTATION OF THE PERFORMANCE OF FRONT OFFICE DEPARTMENT EMPLOYEES IN SERVING GUESTS AT WHITE ROSE KUTA RESORT VILLAS & SPA - Ni Putu Nadira Pebriyanti; I Wayan Jendra; I Ketut Suarja; Cokorda Istri Sri Widhari (Journal of Applied Sciences in Travel and Hospitality, 2018)
The purpose of this study is to determine the influence of knowledge, skills, and attitudes of the employee to the performance of employees in the front office department in serving the guests. This study uses survey method using primary data in this case is front office employees and secondary data sourced from companies and books of literature. The sampling technique in this research is Saturated Sampling Technique with the number of small relative population, less than 30 people. In this study population of 29 employees, all front office department at White Rose Kuta Resort Villas & Spa will be used as respondents by using saturated sampling technique. The related problem is how to apply the performance of front office department employee in serving guest at White Rose Kuta Resort Villas & Spa.